2008
DOI: 10.1074/jbc.m805935200
|View full text |Cite
|
Sign up to set email alerts
|

Differential Roles of the COOH Termini of AAA Subunits of PA700 (19 S Regulator) in Asymmetric Assembly and Activation of the 26 S Proteasome

Abstract: The 26 S proteasome is an energy-dependent protease that degrades proteins modified with polyubiquitin chains. It is assembled from two multi-protein subcomplexes: a protease (20 S proteasome) and an ATPase regulatory complex (PA700 or 19 S regulatory particle) that contains six different AAA family subunits (Rpt1 to -6). Here we show that binding of PA700 to the 20 S proteasome is mediated by the COOH termini of two (Rpt2 and Rpt5) of the six Rpt subunits that constitute the interaction surface between the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
187
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(196 citation statements)
references
References 44 publications
9
187
0
Order By: Relevance
“…This analysis was conducted principally in vitro using isolated peptides corresponding to the C termini of the proteins or with various homomeric protein complexes (20,21,(23)(24)(25). Therefore, to test the relative roles of the three HbYX motifs of the Rpt subunits in cellular assembly of mammalian 26 S proteasome, we repeated the analysis described above with FLAG-Rpt proteins whose HbYX motifs were deleted.…”
Section: C-terminal Hbyx Motifs Of Two Rpt Subunits Rpt5 and Rpt3 Amentioning
confidence: 99%
See 3 more Smart Citations
“…This analysis was conducted principally in vitro using isolated peptides corresponding to the C termini of the proteins or with various homomeric protein complexes (20,21,(23)(24)(25). Therefore, to test the relative roles of the three HbYX motifs of the Rpt subunits in cellular assembly of mammalian 26 S proteasome, we repeated the analysis described above with FLAG-Rpt proteins whose HbYX motifs were deleted.…”
Section: C-terminal Hbyx Motifs Of Two Rpt Subunits Rpt5 and Rpt3 Amentioning
confidence: 99%
“…Support for an important role of HbYX residues in these processes comes from both in vitro and cellular studies. For example, in vitro reconstitution of 26 S proteasome from purified 20 S proteasome and PA700 is abrogated when the HbYX residues of Rpt2 and Rpt5 are enzymatically removed (24). Moreover, Rpt3 lacking its HbYX residues is defective for incorporation into 26 S proteasome in mammalian cells (25).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Its barrel-shaped 20S peptidase is capped by a 19S regulator, a heterohexamer of Rpt subunits. Complex chemical modification and MS studies revealed that binding of 19S is mediated by the C-termini of only two Rpt subunits to dedicated sites on the proteasome and play nonequivalent roles in the asymmetric assembly and activation of the 26S proteasome (Gillette et al, 2008). Cryo-EM has shown that substrate-induced rearrangement of the ATPase subunits results in seven-fold symmetry of the peptidase barrel (Matyskiela et al, 2013).…”
Section: C Pentameric Ligand-gated and Mechanosensitive Channelsmentioning
confidence: 99%